PENGARUH PEMBERIAN PUDING BAYAM (amaranthus Tricolor L.) TERHADAP KADAR GULA DARAH PADA LANSIA DI WILAYAH KERJA PUSKESMAS TANGGULANGIN - Ratna Aminati, Fifi; Yuni Yastutik, Iryani (LPPM STIKES HUSADA JOMBANG, 2023)
Diabetes Mellitus is a condition in which glucose levels exceed normal values because the body cannot use insulin produced effectively. This study aims to determine the effectiveness of giving red spinach pudding to blood sugar levels in elderly diabetes mellitus in the work area of Tanggulangin Public Health Center. This research method uses quasi experiment with the design of one group pre test post test design. The population in this study were elderly in the work area of Tanggulangin Public Health Center with 216 elderly people. Blood sugar level measurements were taken using the Easy Touch GCU tool. Samples were taken using Simple random sampling with a total sample of 19 people. Data analysis using the Wilcoxon test. The results showed that there were differences in blood sugar levels before and after administration of red spinach pudding (p = 0.001), with a decrease in mean blood sugar levels of 75.32 ± 42.22 mg / dl. The conclusion is that there is an effect of giving red spinach pudding to blood sugar levels in elderly diabetes mellitus in the work area of Tanggulangin Public Health Center